The Sense of Being Watched Is Modulated by Arousal and Duration of the Perceptual Episode. (December 2017) - Hesslinger, Vera M.; Carbon, Claus-Christian; Hecht, Heiko
The mere presence of a depiction of eyes can elicit a sense of being watched in the perceiver. To this date, the factors affecting the intensity of this sense of being watched, however, have not been investigated. In the present experiment, we tested the impact of two potentially relevant variables: arousal (manipulated using specific musical pieces) and duration of the perceptual episode (manipulated using presentation times of 200 ms and 10 s, respectively). We asked participants to report how intensely they felt being watched while we exposed them to various observation cues ranging from human eyes to surveillance cameras. We found that, on average, reported intensities were higher if participants were in a state of relatively higher arousal and if the perceptual episode during which the respective observation cues were presented lasted long enough (10 s) to allow more than a first glance. Scientific and practical implications are briefly discussed.